EVALUASI DOKUMEN PERENCANAAN TEKNIS REHABILITASI GEDUNG KANTOR BALAI PRASARANA PERMUKIMAN WILAYAH (BPPW) SUMSEL DALAM BIDANG STRUKTUR DAN BAHAN SESUAI DAFTAR SIMAK SE DJCK 04 TAHUN 2022 - Yani Octa Piyanti; Anggi Purnama Sari Dewi (Rang Teknik Journal, 2026)
The construction of government office buildings requires technical planning documents that comply with national standards. This study aims to evaluate the technical planning documents for the rehabilitation of the South Sumatra Settlement Infrastructure Agency (BPPW) Office Building, focusing on structural and material aspects based on Checklist SE DJCK 04 of 2022. A descriptive qualitative method was applied through document analysis and technical discussions. The evaluation covers legal compliance, building description, document completeness, normative references, material specifications, structural system, load analysis, structural calculation, and construction detailing. Results indicate that the planning documents generally meet technical standards, though some discrepancies were found, such as incomplete geological maps, absence of wind load analysis, and inconsistencies in material specifications across documents. In conclusion, the documents are deemed suitable as a project implementation guide, with recommended improvements in cartography, lateral load analysis, and cross-document harmonization. Suggestions are provided to enhance the integrity of technical documentation through normative updates and cross-validation to ensure optimal safety and construction quality.Keywords: Technical Evaluation, Building Structure, Material Specification, Checklist, Building Rehabilitation